Analisis Pengaruh Bauran Pemasaran Jasa Terhadap Minat Pengunjung Pada Obyek Wisata Museum Kesehatan Dr. Adhyatma, MPH Surabaya - Ayun Maduwinarti (Universitas 17 Agustus 1945 Surabaya, 2014)
The role of museums in Indonesian society is still very minimal. From a marketing perspective, it can be said museum in Indonesia have not been utilizing the concept of marketing communication. One of the museum in Surabaya is the Museum of Health Dr. Adhyatma, MPH. For the manager of the museum 's need to pay attention to the factors that can stimulate consumers are sourced from marketers or often called the marketing mix, such as: product, price, promotion, place, people, process, physical evidence, so as to improve customer service visit the visitor's interest Health Museum of Dr. Adhyatma, MPH Surabaya. This research was conducted in order to determine and analyze the influence of eight factors of marketing mix to interest visitors to visit the Museum of Health Dr Adhyatma, MPH Surabaya. In terms of the method used, this study is a conclusive studies with statistical hypothesis testing coupled with the aim to test the hypotheses put forward. Form of survey research design, the research conducted by distributing questionnaires. The samples were 135 visitors Museums of Health Dr. Adhyatma, MPH Surabaya. The scale of measurement in this study is using a Likert Scale. The analysis technique used Structural Equation Modeling ( SEM ). The conclusion that can be drawn from this finding is variable product, price, promotion, place, people, process, physical evidence, and customer service significant positive effect on the interest of visitors to the Museum of Health Dr. Adhyatma, MPH Surabaya. In connection with the matter, the manager of the museum needs to provide training to employees on a regular basis and in accordance with their respective sectors, respectively, so that later an employee is able to provide fast service and appropriate expectations of visitors.Keywords: product, price, promotion, place, people, process, physical evidence, customer service and visitor interest